Perilaku Politik Pemilih Pada Pemilihan Kepala Daerah Di Kota Madiun (Studi Perilaku Pemilih pada Pilkada di Kota Madiun - Agus Prasetya; Adi Suparto (LPPM Universitas Trunojoyo Madura, 2014)
Social facts indicate that the local democratic process, which should be able to run properly and correctly according to the purpose, namely to increase political participation from the people to elect a leader, has yet to produce maximum results. This study is a qualitative one of the research procedures that produce data diskripif form of speech, writing, and the behavior of those who observed. Techniques of data collection in this study with the techniques of observation, in- depth interviews (depth interview) on the subject of research (voters) with snowball technique that is on the list of voters in the Election Commission. Researchers used several theoretical studies, among others: social exchange theory, the theory of social behavior, the theory of social action. Madiun city election results, the study subjects consisted of voters, the people give answers, that the victory in the elections on 29-Aug-2013 by Line because of social capital and economic capital. Candidates for Mayor and Vice Mayor Madison city that has political experience, economic capital, and social capital that both won the election of 2013. The results of the election in accordance plenary recapitulation Election Commission on 9 September2013, as follows: Line: 49.50%, Pari: 33.50%. top-Care: 2.50%. Clouds- 19: 7.6%% Pure: 6:30% and ARH: 1.95% of the number of voters in the final voters list 146 634.voters.